2006
DOI: 10.1093/jn/136.7.1766
|View full text |Cite
|
Sign up to set email alerts
|

Red Grape Juice Polyphenols Alter Cholesterol Homeostasis and Increase LDL-Receptor Activity in Human Cells In Vitro

Abstract: Red grape juice (RGJ) polyphenols have been shown to reduce circulating levels of LDL cholesterol and to increase LDL receptor activity. To explore the effect of RGJ-derived polyphenols on intracellular cholesterol homeostasis, human hepatocarcinoma HepG2 and promyelocytic HL-60 cell lines were incubated in serum-free medium, with or without LDL, in the presence or absence of RGJ. In the presence of LDL, RGJ increased both the activity and cell surface expression of the LDL receptor, and increased the cell tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 46 publications
4
35
0
3
Order By: Relevance
“…Interestingly, a significant positive correlation between the phenolic content in the oil and linoleic acid-rich moieties was observed. This phenomenon was associated with a possible effect of phenolics on the modulation of the gene and protein expression or activities of key enzymes involved in TG transport and metabolism, like LPL [18], apo B48, microsomal TG transfer protein (MTP) [19], or receptors involved in the uptake of VLDL by the liver [20].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a significant positive correlation between the phenolic content in the oil and linoleic acid-rich moieties was observed. This phenomenon was associated with a possible effect of phenolics on the modulation of the gene and protein expression or activities of key enzymes involved in TG transport and metabolism, like LPL [18], apo B48, microsomal TG transfer protein (MTP) [19], or receptors involved in the uptake of VLDL by the liver [20].…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies on grapes and their derivatives have demonstrated these properties, including protection against cardiovascular diseases [68,69], atherosclerosis [70], hypertension [71], cancer [72], diabetes [73] and neurological problems [74]. The mechanism of action has been attributed to antioxidant activity [75], lipid regulation [76,77], anti-inflammatory effects [78], anti-cancer, antimicrobial, antiviral, cardio protective, neuroprotective, and hepatoprotective activities [1,40,41,48,[79][80][81][82][83].…”
Section: Biological Activity Of Phenolic Compounds Present In Grape Jmentioning
confidence: 99%
“…Concentrated RGJ from the 'bobal' grape variety was purchased from Dream Fruits (Quero, Toledo, Spain) containing 6·4 g total polyphenols/l (gallic acid equivalents), 124 mg anthocyanidines/l and a high concentration of flavonoids, including quercetin, myricetin and traces of (2 )-epicatechin, (þ)-catechin, resveratrol and other phenolic acids; a detailed phenolic composition is described elsewhere (30,36) . Red wine from the Tempranillo variety (kindly provided by María de Maeseneire) was used to prepare dealcoholised red wine (DRW).…”
Section: Reagentsmentioning
confidence: 99%